Strategi Pembangunan Kota Berkelanjutan dalam Mencapai SDGS di Kota Pekanbaru - Agus Mandar; Novita Rany; Zulmeliza Rasyid (Jurnal Zona, 2025)
The implementation of regional autonomy since 25 years has had a significant impact on the development of districts / cities in Indonesia. The high urbanization trend in several provinces on the island of Sumatra such as Riau Province has implications for the growth and development of Pekanbaru City as a center of government, education, business, tourism, services and trade. The Sustainable City Development Strategy in Achieving SDGs in Pekanbaru City uses the Pentagon Prism theory from Nijkamp (1994) as a development paradigm and New Urban Agenda (NUA) to guide the Regional Government to achieve the Sustainable City vision of Pekanbaru Smart City Madani, namely (1) Socioware, (2) Orgware, (3) Finware, (4) Technoware (5) Ecoware which is combined with the Smart City concept which consists of 6 indicators, namely (1) Smart Governance, (2) Smart People, (3) Smart Economy, (4) Smart Transportation, (5) Smart Environment, (6) Smart Living. From the 11 indicators above, the Pekanbaru City Government has carried out various policies both in the form of regulations in the form of Mayor Regulations, as well as in the form of programs and activities that have been implemented since 2019. However, because the problems faced are very complex while resources are limited, these indicators have not been met optimally. As a strategy to accelerate the achievement of SDGs that must be achieved by 2030, the Pekanbaru City Government collaborates with relevant stakeholders (collaborative governance).